1991
DOI: 10.1016/0005-1098(91)90127-n
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate automation—Integrating technical, human, organizational, economic and cultural factors

Abstract: Key Words--Social effects of automation; human-machine systems; human factors; organizational, economic and cultural factors; manufacturing processes; process industries; human-centered design; sociotechnical design.Almtrad--Automation technology, including digital computer and communication techniques, is being applied in an ever-increasing range of private and public spheres, and reaching third world cultures not previously exposed to such technology. It is engineers' responsibility to consider the direct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The emergence of expert systems revolutionized science. Since 1990, Martin et al (1990) have shown that "although expert systems have proved successful in solving intractable with conventional numerical methods, their role remains limited to support functions, ......"; the conclusion provided by an ES and/or other instruments in the IA must be interpreted by human experts within a business organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emergence of expert systems revolutionized science. Since 1990, Martin et al (1990) have shown that "although expert systems have proved successful in solving intractable with conventional numerical methods, their role remains limited to support functions, ......"; the conclusion provided by an ES and/or other instruments in the IA must be interpreted by human experts within a business organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technocentric approach focuses mainly on optimization of automatic operations in production and on the shop floor (Martin et al, 1991). The effects of this strategy are often inflexible systems and a higher sensitivity to disturbances due to lack of concern for human factors.…”
Section: Tablementioning
confidence: 99%
“…A CIM system is part and parcel of the infrastructure of the enterprise. Thus, CIM systems designed on the conventional "automation" paradigm, are disasters to come (see Martin et al, 1990).…”
Section: The Fallacy Of the Automation Paradigmmentioning
confidence: 99%